Anisotropy of the surface energy of silicides of some metals - Yurov, V.M.; Goncharenko, V.I.; Oleshko, V.S.; Makhanov, K.M. (KU Publ., 2021)
An empirical model of a solid surface is proposed in the article. The thickness of the surface layer is described in terms of one parameter – the atomic volume of an element or its compounds. Surface energy is also expressed through one parameter – the melting point of a chemical element or crystal. The model proposes equations that allow calculating the thickness of the surface layer and surface energy for each face of the crystal. As an example, calculations of these values are made for silicides of some metals with crystal structures of cubic, hexagonal and rhombic systems. For cubic silicides, the thickness of the surface layer is 3-9 nm, and the number of monolayers is 7-16. Studies of metal deposition on silicon faces have shown that silicon silicide is formed on the (111) face, which has the highest surface energy. The reaction on the (100) face occurs only on the oxidized surface. In hexagonal silicides, anisotropy is seen, both in the values of the thickness of the surface layer and in the values of the surface energy. For example, during the formation of chromium disilicide on the (111) face in the c direction, it was found that the sizes of the islands become larger than on the (001) face. The authors designate that the thickness of the surface layer and the specific surface energy for cubic, hexagonal, and rhombic crystals significantly differ from them. What is the difference? First, the difference between the atoms of chemical elements from the periodic table and their compounds depends, first of all, on their electronic structure, which forms this or that interaction potential. Secondly, the difference between cubic, hexagonal and rhombic crystals lies in their relationship with Poisson's ratio and Young's modulus, that is, on two material parameters. Third, the thickness of the surface layer between cubic, hexagonal, and rhombic crystals also differs in only one parameter – the atomic (molar) volume of the crystal. However, the analysis of all the patterns still needs to be carefully analyzed.
Кейбір металдардың силицидтерінің беттік энергиясының анизотропиясы
Анизотропия поверхностной энергии силицидов некоторых металлов
Keywords: metal silicide; surface energy; thickness of the surface layer; solid; chemical element; crystal; surface layer; Poisson's ratio; Young's modulus